The NAO Impact on Droughts in the Mediterranean Region - Vicente Serrano, Sergio M.; López-Moreno, Juan I.; Lorenzo-Lacruz, Jorge; El Kenawy, Ahmed M.; Azorín-Molina, César; Morán-Tejeda, Enrique; Pasho, Edmond; Beguería, Santiago; Angulo-Martínez, Marta (2011)
18 Pags., 7 Figs. The definitive version is available at: http://www.springerlink.com/content/978-94-007-1371-0/ This chapter shows the influence of the North Atlantic Oscillation (NAO) on droughts in the entire Mediterranean region between 1901 and 2006. The analysis has been based on identification of positive and negative NAO winters and also detection of the anomalies of drought severity by means of the Standardized Precipitation Evapotranspiration Index (SPEI). The analysis is focussed on the winter NAO. Nevertheless, given that the SPEI drought indicator can be obtained at different time-scales, the study shows how the effects of the winter NAO on droughts are propagated for the following months when long time scales are considered. In general, during the positive phases, the negative SPEI averages are recorded in Southern Europe (the Iberian Peninsula, Italy and the Balkans), areas of Turkey and northwest Africa. On the contrary, the SPEI averages are found positive in northeast Africa. The opposite configuration, but with some differences in the spatial patterns and the magnitude of the SPEI averages, is found during the negative NAO years. The findings of this study should be of great applicability in terms of developing early warning systems. The established relationships between NAO phases and drought indices seem appropriate for drought prediction over large areas of the Mediterranean basin. This work has been supported by the research projects CGL2008-01189/BTE and CGL2006-11619/HID financed by the Spanish Commission of Science and Technology and FEDER, EUROGEOSS (FP7-ENV-2008-1-226487) and ACQWA (FP7-ENV-2007-1- 212250) financed by the VII Framework Programme of the European Commission, and “La nieve en el Pirineo aragonés: Distribución espacial y su respuesta a las condiciones climáticas” Financed by “Obra Social La Caixa” and the Aragón Government. Peer reviewed